Fracture behavior of minimally invasive, posterior, and fixed dental prostheses manufactured from monolithic zirconia - Bömicke, Wolfgang; Rues, Stefan; Hlavacek, Verena Anna; Rammelsberg, Peter; Schmitter, Marc (Journal of esthetic and restorative dentistry, 2016)
Objectives To compare ultimate fracture load (Fu), load at first damage (F1d), and fracture pattern for posterior fixed dental prostheses (FDPs) manufactured from translucent, yttria-stabilized zirconia polycrystal. Methods Premolar-size FDPs in 4 test groups (n = 16/group) were constructed as veneered complete crown-retained (group 1), monolithic complete crown-retained (group 2), monolithic partial veneer crown-retained (group 3), or monolithic resin-bonded (group 4) prostheses with minimum zirconia wall thickness (0.5 mm). Adhesively cemented to metal abutments, half of the prostheses were artificially aged by use of 10,000 thermocycles (6.5°C/60°C) and 1,200,000 chewing cycles (F = 108 N), before fracture loading. Statistics included two-way non-parametric ANOVA and Dunn-Bonferroni post-hoc tests (α = 0.05). Results None of the restorations failed during artificial aging. Fu was affected by test group (p < 0.001); F1d was also affected by the factor combination of test group and aging (p = 0.001 for test group; p = 0.049 for test group*aging). Mean Fu for all groups exceeded 1000 N; it was comparable for group 1 and group 2 and statistically significantly higher for group 2 and group 3 than for group 4 (p < 0.01). Fracture usually occurred through the retainer wall. F1d = 200 N was determined for individual samples in group 1 (chipping) and group 3 (local debonding). Conclusions Fu of all the restorations was adequate for clinical use. Complications might, however, be expected at forces below 500 N for veneered prostheses (chipping) as well as for monolithic partial veneer crown-retained prostheses (local debonding). Clinical Significance With regard to fracture behavior, all-ceramic complete crown-retained fixed dental prostheses (FDP) manufactured from monolithic zirconia, with a retainer wall thickness of 0.5 mm, might be suitable for use as a conservative alternative to their veneered counterparts in the rehabilitation of posterior tooth loss. Monolithic zirconia resin-bonded FDP might, moreover, be a viable alternative to resin-bonded FDPs with metal adhesive retainers in posterior arches, with improved esthetics and biocompatibility. The performance of both should, however, be verified in clinical trials. (J Esthet Restor Dent 28:367-381, 2016)
Gesehen am 14.05.2020